2020
DOI: 10.12968/ijtr.2018.0130
|View full text |Cite
|
Sign up to set email alerts
|

Clinicians' involvement in data collection for portfolio research: impact on their clinical practice and perception of research

Abstract: Background/Aims Physiotherapists generally have a positive view of research, but have identified a number of barriers to taking part, and have expressed challenges when attempting to integrate research findings into their practice. The aim of this study was to describe the self-reported impact of collecting data for a multicentre research study on physiotherapists' clinical practice. Methods Convenience sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(36 citation statements)
references
References 9 publications
2
34
0
Order By: Relevance
“…Four researchers created bespoke survey tools to answer their research questions (Das et al, 2008;Khera et al, 2018;Litjens et al, 2013;Sweeting et al, 2020), while Tranmer et al (2002) used a research utilisation questionnaire (RUQ) which asked respondents to rate their use of research in the clinical setting. Three of the bespoke surveys focussed on respondents' knowledge of trial results, and self-reported impact of the results on clinical practice (Khera et al, 2018;Litjens et al, 2013;Sweeting et al, 2020). A combination of closed questions and Likert scale responses were included, with some questions leading to open-ended responses (Khera et al, 2018;Sweeting et al, 2020).…”
Section: Research Methods and Topicsmentioning
confidence: 99%
See 4 more Smart Citations
“…Four researchers created bespoke survey tools to answer their research questions (Das et al, 2008;Khera et al, 2018;Litjens et al, 2013;Sweeting et al, 2020), while Tranmer et al (2002) used a research utilisation questionnaire (RUQ) which asked respondents to rate their use of research in the clinical setting. Three of the bespoke surveys focussed on respondents' knowledge of trial results, and self-reported impact of the results on clinical practice (Khera et al, 2018;Litjens et al, 2013;Sweeting et al, 2020). A combination of closed questions and Likert scale responses were included, with some questions leading to open-ended responses (Khera et al, 2018;Sweeting et al, 2020).…”
Section: Research Methods and Topicsmentioning
confidence: 99%
“…The literature to date has not demonstrated a link between participation in research and subsequent knowledge use, and no research on this topic has been conducted in Australia or NZ or in ICU. Some studies reported no increased knowledge or use of results, despite personal or institutional involvement in a clinical trial even when the RCT showed very high quality evidence (Khera et al, 2018;Majumdar et al, 2002;Shah et al, 2010), while other studies showed mixed results (Kizer et al, 1999;Litjens et al, 2013;Sweeting et al, 2020).…”
Section: Gaps In Knowledgementioning
confidence: 99%
See 3 more Smart Citations